Otoritas Hadis Riḍā‘ dan Dinamika Bank ASI: Menuju Formulasi Fikih Maḥram yang Responsif - Zikri Darussamin (AL-MUTSLA, 2026)
'This article examines the authority of the riḍā‘ hadith in the construction of mahram law and its relevance to the practice of milk banks in a contemporary context. Starting from the problem of the increasing need for breast milk donors and the complexity of maḥram relationships that this creates, this study aims to reconstruct a contextual understanding of the riḍā‘ hadith in order to formulate maḥram jurisprudence that is responsive to modern socio-medical developments. This study employs a qualitative approach using the methods of takhrij al-hadith, criticism of the isnad and matn, as well as an analysis of the interpretations of classical and contemporary scholars. Textual analysis is conducted by examining the authenticity, wording, and substance of the hadith, while contextual analysis highlights the socio-historical background of the hadith’s emergence, breastfeeding practices during the time of the Prophet, and its legal implications in the context of modern society. Research findings indicate that the hadith of ar-riḍā‘ possesses strong validity within the chain of transmission and serves as the primary foundation for the laws of wet-nursing in Islamic jurisprudence, particularly regarding the limit on the number of wet-nursing sessions, the scope of mahram relationships, and the legal consequences of marriage. In the context of breast milk banks, there has been a shift in relational patterns that demands clarity regarding the identities of donors and recipients to avoid confusion regarding lineage and mahram status. Therefore, an adaptive fiqh formulation is required while upholding the principle of hifẓ al-nasl, through strict regulations and an approach based on maqāṣid al-syarī‘ah.